Perancangan Multimedia Interaktif Pengenalan Alat Transportasi Untuk Taman Kanak-Kanak - Anik Ismiwati; Bagus Maulana Syah; Refi Difa Arcelia; Riyan Abdul Aziz (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The education sector must utilize the latest technology in the classroom in the era of globalization and rapid advances in information technology. Using text, graphics, audio, and video together, interactive learning materials have been proven to increase student understanding and engagement. Kindergarten (TK) is a place where children are introduced to the environment and the basic principles of learning. Introducing children to various types of transportation is believed to be very important because it is the first step in helping them broaden their horizons and become familiar with the types of transportation in their environment. Apart from that, children are very interested in and liked transportation, so it must be packaged attractively so that it can arouse their curiosity in learning.